The Understanding Strategy of Worship to Exceptional Children - Syamsuri; Kaspullah; Aslan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
The Artiel examines the strategy of understanding worship in exceptional children. This research was conducted at the Sekolah Luar Biasa Negeri Sambas, Sambas Regency, West Kalimantan. This study focuses on the aspects of how the strategies used in Islamic religious education teachers provide understanding to children in foreign schools. This research uses a qualitative approach. The results of the analysis of this study conclude that the strategies used by Islamic religious education teachers include accustoming congregational prayer and accustoming good morals in the school environment and at home, Islamic religious education teachers report learning outcomes to parents, Islamic religious education teachers provide good examples of students, Islamic religious education teachers run the principal's program, Islamic religious education teachers provide mutual supervision of students in the teaching and learning process.